2005
DOI: 10.5301/hip.2008.1832
|View full text |Cite
|
Sign up to set email alerts
|

Early rehabilitation comparing hip resurfacing and total hip replacement

Abstract: Hip resurfacing arthroplasty (RS) is said to be an operation that is suitable for the younger osteoarthritic population, allowing them to rehabilitate more rapidly. We wished to establish whether this was true and compared 35 consecutive RS (33 patients) with 41 consecutive total hip replacements (THR) (40 patients) and looked specifically at postoperative pain, speed of rehab-ilitation and length of hospital stay. A rehabilitation score was used. RS patients were significantly younger than THR patients (mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…One study reported that more HRA patients returned to work (96%) and heavy to moderate activities (72%) 1 year postoperatively than THA patients (66% and 39%, resp.). However, both groups were not completely comparable as the mean BMI of the HRA group was significantly lower (Lilikakis et al, 2005). Gender influences functional outcome scores as Amstutz et al found, in a case series of 923 patients, that women improved more in walking, function, and the SF-12 mental component, whereas males improved more in activity at an average follow-up of 7 years (Amstutz et al, 2011).…”
Section: Cementing Techniquementioning
confidence: 99%
“…One study reported that more HRA patients returned to work (96%) and heavy to moderate activities (72%) 1 year postoperatively than THA patients (66% and 39%, resp.). However, both groups were not completely comparable as the mean BMI of the HRA group was significantly lower (Lilikakis et al, 2005). Gender influences functional outcome scores as Amstutz et al found, in a case series of 923 patients, that women improved more in walking, function, and the SF-12 mental component, whereas males improved more in activity at an average follow-up of 7 years (Amstutz et al, 2011).…”
Section: Cementing Techniquementioning
confidence: 99%
“…With regard to offset restoration, Loughead et al reported that hip resurfacing does not restore hip mechanics as accurately as THA in patients who received a Birmingham Hip Resurfacing prosthesis [ 76 ] . Lilikakis et al [ 77 ] reported no benefi ts in regard to rehabilitation. Crawford and Villar found greater acetabular bone resection than with THR in an in vitro study [ 78 ] .…”
Section: Current Resurfacing Prosthesesmentioning
confidence: 99%
“…It has also been shown that individuals can improve their level of activity postoperatively [14]. There have been several complications reported such as limited range of motion [15][16][17], failed femoral components [18], femoral fracture [19], avascular necrosis [20], ion excretion [21,22] and tissue Synovitis [23,24]. These appear to be the result of a surgical learning curve as well as the need to modify the initial implant design [25].…”
Section: Introductionmentioning
confidence: 99%